Incidence of syphilis in pregnant women in the countryside of são paulo from 2018 to 2020 - Andrade, Bianca Garcia Botelho de; Fernandes, Jaqueline; Tonon, Amanda Fedozi; Ribeiro, Eleusa Gomes Muniz; Ramos, Rogério Rodrigo; Neto, José Martins Pinto; Lozano, André Wilian (International Journal for Innovation Education and Research, 2022)
Syphilis is caused by the bacterium Treponema pallidum and is transmitted sexually, hematogenously or vertically, and may occur in any time of pregnancy. It is one of the major concerns and high rates of pregnant women with syphilis, which leads to congenital syphilis. The aim of this study was to investigate the incidence of syphilis in pregnant women in the state of São Paulo from 2018 to 2020 in epidemiological surveillance. The study is an epidemiological, descriptive observational research of quantitative analysis with secondary data, notified in the Notifiable Diseases Information System (SINAN), which is the database of the Department of Informatics of the Unified Health System (DATASUS), of pregnant women with syphilis, between 2018-2020. The collection of secondary data was authorized of São Paulo State. We found 50 women with unspecified syphilis in the last 3 years, of these 36 are pregnant women with syphilis and 7 cases of congenital syphilis. There has been a large increase in pregnant women with syphilis in the last year, however, there has been an eradication of congenital syphilis during this period. With this, it can be emphasized the importance of screening and early treatment of pregnant women in the Primary Health Care Network to promote health promotion and to offer quality of health services to mothers.